Social and Tradition In Local Knowledge For Dealing With Nature Disaster - Bahagia - Bahagia; Rimun Wibowo; Fachruddin Majeri Mangunjaya (Universitas Pahlawan Tuanku Tambusai, 2022)
Natural disasters as a result of natural damage due to human behaviour and natural behaviour. The main objective of this research is to find out the traditions and forms of social capital applied by the indigenous people of Urug from the perspective of key figures in dealing with disasters. At the same time find the mitigation that is done in the face of disasters. The research method used is the ethnographic method qualitatively. The sample collection technique in this study used the purposive sampling technique. The results of the study show that helping is a tradition to help residents affected by disasters. The unaffected community provided basic needs including rice, food, clothing, blankets and shelter before aid from the government arrived. This tradition is related to the principle of brotherhood in society. The findings are that there is disaster literacy carried out to respond to disaster events such as the relationship between river areas and the potential for disasters to occur. Another way of responding is to become a trader outside the village, such as going to trade in big cities so that they get additional income to overcome economic problems. In fact, there is a wise way to do this, namely, when someone owes a debt to someone else, someone who has debt can replace the debt not with money but in other ways such as working at the person's place until the debt can be paid off.